KANDUNGAN LOGAM BERAT Pb, Cd, Cu, Zn DAN Ni DALAM AIR LAUT DAN SEDIMEN DI MUARA SUNGAI MEMBRAMO, PAPUA DALAM KAITANNYA DENGAN KEPENTINGAN BUDIDAYA PERIKANAN (Makara Journal of Science, 2023)
Heavy Metals Content Pb, Cd, Cu, Zn And Ni In Sea Water And Sediment In Membramo Estuary And Its Relationship With Fishery Cultivation. Obervation on heavy metals Pb, Cd, Cu, Zn and Ni content in Jakarta Bay were carried out in August 2003. The results showed that the Pb, Cd, Cu, Zn, and Ni content still in line with threshold value stated by for fisheries. By the all, in sea water Zn content is higher compared to the others, while in sediment Ni is higher. This data showed the result show that on waters of Membramo River Zn and Ni waste than others elements.